1967
DOI: 10.1002/aic.690130444
|View full text |Cite
|
Sign up to set email alerts
|

Temperature distribution in a fin partially cooled by nucleate boiling

Abstract: When heat is transferred from a fin into a nearly saturated liquid, nucleate 'boiling may set in if the temperature on the fin is sufficiently higher than the liquid's saturation temperature (1). Such a mode of heat transfer would be very efficient because of the high heat transfer coefficient of nucleate boiling over an extended surface area. Prior to this report, only complicated numerical solutions for nucleate boiling from a fin had been proposed (1, 2 ) . The purposes of this report are to present a simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

1970
1970
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 2 publications
1
14
0
Order By: Relevance
“…In many applications, various heat transfer modes, such as convection, nucleate boiling, transition boiling, and film boiling, the heat transfer coefficient are no longer uniform. A fin with an insulated end has been studied by many investigators [5][6][7][8][9]. Most of them are immersed in the investigation of single boiling mode on an extended surface.…”
Section: Introductionmentioning
confidence: 99%
“…In many applications, various heat transfer modes, such as convection, nucleate boiling, transition boiling, and film boiling, the heat transfer coefficient are no longer uniform. A fin with an insulated end has been studied by many investigators [5][6][7][8][9]. Most of them are immersed in the investigation of single boiling mode on an extended surface.…”
Section: Introductionmentioning
confidence: 99%
“…Since the temperature at the junction of two segments is known, the segment length and heat transfer rate in the k-section can be calculated from Eqs. (4), (5), (8) and (11). In case the fin tip is subject to transition boiling, Eq.…”
Section: Solution Proceduresmentioning
confidence: 99%
“…In the analytical study of multi-boiling from a fin, Lai and Hsu [8] presented a one-dimensional model to study the heat transfer characteristics of a fin partly cooled by nucleate boiling and partly by convection. Good agreements were observed between their results and the experimental data of Haley and Westwater [5].…”
Section: Introductionmentioning
confidence: 99%
“…(8), (11) and below # local temperature difference between a fin and environment, t À t a (K) u relative percent discrepancy between the closedform and recurrent solutions for T e and T (%) w fin aspect ratio (fin height to half thickness or half radius ratio), Bi l /Bi x = h e /h x=0 ratio of heat transfer coefficients on the fin tip and lateral surfaces, a e /a Subscripts and superscripts a ambient medium (environment) b fin base (at X = 1) e fin tip (at X = 0) * fin with an insulated tip been presented in the plots of fin efficiency vs thermo-geometrical parameter of a fin. But the latter parameter involves the heat transfer coefficient calculated locally and averaged along the fin.…”
Section: Introductionmentioning
confidence: 97%
“…The latter dependence is usually expressed as a power function of #, h = a# n with constant a and n. The 1-D steady-state problem of heat conduction, governed by the power-law type temperature dependent local heat transfer coefficient for a single straight fin of uniform cross section is reduced to the solution of ordinary nonlinear second-order differential equation with two boundary conditions. The analytical and numerical solutions of such problems for the definite values of n made their appearance in the middle 1960s-early 1970s (see, for example, papers [6][7][8][9]). Ü nal [10][11][12] showed that the explicit analytical closed-form solutions can be obtained only for several definite values of n = À4, À1, and for n = 0.…”
Section: Introductionmentioning
confidence: 99%